O problema do eu e da consciência: um estudo da primeira parte da obra A doença para a morte de Søren Kierkegaard - Mozine, Maria Herminia de Oliveira (2019)
The aim of this dissertation is to analyze the first part of Søren Kierkegaard’s The Sickness Unto Death, written in 1849, with the purpose to analyze the man’s problem of becoming himself, to be aware of his freedom, and his responsability for its existence. From the anthropological definition of man as spirit, and the spirit as self, the author uses the concepto f despair to demonstrate how difficult it is to go through the dialectic of self, to accomplish the task of becoming oneself and to attain self awareness. As a person is born human, but not born with the self builted, it is necessary to accomplish the synthesis that is the self within another synthesis, s the concept of despair to demonstrate how difficult it is to navigate the dialectic of self, realizing the task of becoming himself and achieve the selfconsciousness. As long as a person is born human, but not born with the self already built, it is necessary to do the synthesis that is the self within other synthesis, which is the man. This work will hemeneytically analyze the researched book, through reviewing the existing literature. It follows that if the man is not free, or he is dependente and submissive of the general will, when is trapped in immediacy, or he is desperate and closed in himself, because he has not effectively become himself; this shows the distance from God, but there is the possibility to establish a relationship with Him, because man is na inconclusive synthesis. And, that the self-awareness that can come to yourself is to be a desperate or a sinner, living therefore Always in the tension between reason and Faith and between the despair and sin.